Sea urchin Tetrapigus niger as a biological marker of oxidative stress - Huerta Canales, Doris (2000)
In this research the sea urchin Tetrapigus Niger has been used as a model to study oxidative stress to measure the lipid peroxidation in sperm nuclei. Oxidative stress was observed in sperm nuclei with and without hydrogen peroxide, which is a good free radicals generating system.